PENGARUH KUALITAS PELAYANAN KEPERAWATAN TERHADAP KEPUASAN PASIEN PADA RSUD PANGLIMA SEBAYA KABUPATEN PASER - Masitah Masitah; Anthonius Junianto Karsudjono (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
The purpose of this study is to determine and analyze at Panglima Sebaya Regional General Hospital, Paser Regency, East Kalimantan, related to: 1) The variables of nursing service quality (consisting of physical evidence, reliability, responsiveness, assurance, and empathy) simultaneously influence patient satisfaction. 2) The variables of nursing service quality (consisting of physical evidence, reliability, responsiveness, assurance, and empathy) partially influence patient satisfaction. 3). Among the variables of nursing service quality (consisting of physical evidence, reliability, responsiveness, assurance, and empathy), which one has the dominant influence on patient satisfaction.This research is quantitative. The population was 6,517 patients who visited Panglima Sebaya Regional Hospital between January and March. The sample consisted of 98 patients who visited Panglima Sebaya Regional Hospital. The sampling technique used was accidental sampling. The analysis model used was multiple linear regression analysis.The results of the study found that: 1) The quality of nursing services (consisting of physical evidence, reliability, responsiveness, assurance, and empathy) had a significant simultaneous effect on patient satisfaction at Panglima Sebaya Regional Hospital, Paser Regency. 2) The quality of nursing services (consisting of physical evidence, reliability, responsiveness, assurance, and empathy) had a significant partial effect on patient satisfaction at Panglima Sebaya Regional Hospital, Paser Regency. 3) Assurance was the variable that had the dominant effect on patient satisfaction at Panglima Sebaya Regional Hospital, Paser Regency.